Online Machine Translation: The Students’ Perspective during Quarantine Period Learning Activity - Ratih Laily Nurjanah; Deswandito Dwi Saptanto (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
The role of internet nowadays leads to the increase of online translation usage. The online translation offers various kinds of machine translation besides the-popular- Google Translate. The purpose of this research is to determine the students’ perspective on online machine translation they can easily found on internet related to the learning process on translation study during the quarantine period.. The research questions are; 1) What are the good sides of using online machine translation? 2)What are the shortages of using online machine translation? 3)How does online machine translation help students during learning activities on quarantine period? Online machine translation is automated translation or “translation carried out by a computer” with the internet connection. The subjects of this study were 6th semester students at English Literature Department of Universitas Ngudi Waluyo who had taken subjects related to translation. The research was conducted by delivering survey with google form to gather students’ perspectives. From the results, it is concluded that students were familiar with Google Translation as the online machine translation. Students stated that online machine translation often gives ambiguous translation. The use of online machine translation is helpful especially in terms of saving time. In conclusion, to keep up with the development of digital era, students need to be introduced to various online machine translation to help them work faster and keep improving their translation skill to back up the defects of online machines translation.